The guiding significance of the Marxist classic writers’ thoughts on the theory of historical synergy for Chinese-style modernization - Huang, Yuyin (International Theory and Practice in Humanities and Social Sciences, 2025)
The historical synergy theory of Marxist classic writers is the enrichment and development of historical materialism, which has rich and profound content. Through the analysis of the origin and connotation of the theory of historical synergy, the author deeply understands the implication and significance of the theory of historical synergy. In the objective reality, combined with the characteristics of Chinese modernization and the application of historical synergy theory in the process of Chinese modernization, the importance of historical synergy theory to Chinese modernization is clarified. In theory, this paper analyzes the compatibility of historical synergy theory and Chinese modernization, clarifies the necessity of historical synergy theory to guide Chinese modernization theory, and puts forward its important inspiration and practical guidance to Chinese modernization.